PENERAPAN MODEL KOOPERATIF TGT BERBANTUAN MEDIA QUESTION CARD UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF MURID SMP - Erinda Fazila Safitri; Elok Sudibyo (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
This study aimed to analyze the improvement of junior high school students’ cognitive learning outcomes, the implementation of the learning process, and students’ responses after the application of the Teams Games Tournament (TGT) cooperative learning model supported by question card media on the topic of the human digestive system. The research employed a pre-experimental method using a One Group Pretest–Posttest design. The subjects of this study were 30 students of class VIII-B at SMP Bahrul Ulum Surabaya. The indicators of cognitive learning outcomes focused on analytical skills, including differentiating, organizing, and attributing. The results revealed a significant difference between pretest and posttest scores after the implementation of the learning model, with a t-test significance value of Sig. < 0.05. The N-Gain analysis showed an improvement in cognitive learning outcomes of 0.6, which falls into the moderate category. The implementation of the TGT cooperative learning model assisted by question card media was categorized as very good, with a 100% implementation rate. Students’ responses to the learning process were classified as very positive, with an average percentage of 85%, indicating that students were more interested, felt supported, and found it easier to understand the topic of the human digestive system. Based on these findings, it can be concluded that the TGT cooperative learning model assisted by question card media is effective in improving junior high school students’ cognitive learning outcomes. ABSTRAK Penelitian ini bertujuan untuk menganalisis peningkatan hasil belajar kognitif murid SMP, keterlaksanaan proses pembelajaran, serta respons murid setelah penerapan model pembelajaran kooperatif Teams Games Tournament (TGT) yang didukung media question card pada materi sistem pencernaan manusia. Penelitian ini menggunakan metode pre-experimental dengan desain One Group Pretest-Posttest. Subjek penelitian adalah 30 murid kelas VIII-B SMP Bahrul Ulum Surabaya. Indikator hasil belajar kognitif difokuskan pada kemampuan menganalisis yang meliputi aspek membedakan, mengorganisasikan, dan mengatribusi. Hasil penelitian menunjukkan adanya perbedaan yang signifikan antara nilai pretest dan posttest setelah penerapan model pembelajaran, dengan nilai signifikansi uji-t Sig. < 0,05. Analisis N-Gain menunjukkan peningkatan hasil belajar kognitif sebesar 0,6 yang termasuk dalam kategori sedang. Keterlaksanaan pembelajaran dengan model kooperatif TGT berbantuan question card berada pada kategori sangat baik dengan persentase 100%. Respons murid terhadap pembelajaran tergolong sangat positif dengan rata-rata persentase 85%, yang menunjukkan bahwa murid merasa lebih tertarik, terbantu, dan lebih mudah memahami materi sistem pencernaan manusia. Berdasarkan temuan tersebut, dapat disimpulkan bahwa model pembelajaran kooperatif TGT berbantuan media question card efektif dalam meningkatkan hasil belajar kognitif murid SMP.